2019
DOI: 10.1029/2019gl081970
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and Persistent Deposition of Iron Formations for Two Billion Years

Abstract: Composed of chemical precipitates rich in iron and silica, Precambrian iron formations from marine sedimentary records may reveal biogeochemical processes over the first half of Earth history. The limited record of early Archean rock suggests that preservation biases the iron formation record. Like ophiolites, which provide a sparse record of past ocean floor, iron formations deposited on oceanic crust ought to also be rare and preserved only when accreted onto cratons. To correct for potential preservation bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 137 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…The most extensive IF deposition occurred from 2.7 to 2.4 Ga, with a spike again at 1.9 to 1.8 Ga (Figure 1; Bekker et al, 2010). However, when bias is removed by scaling iron content with crustal preservation, a recent analysis suggested that IF deposition likely persisted at near constant rate from 3.8 to 1.8 Ga (Johnson and Molnar, 2019).…”
Section: Iron Formations Evidence Ferruginous Conditionsmentioning
confidence: 96%
See 1 more Smart Citation
“…The most extensive IF deposition occurred from 2.7 to 2.4 Ga, with a spike again at 1.9 to 1.8 Ga (Figure 1; Bekker et al, 2010). However, when bias is removed by scaling iron content with crustal preservation, a recent analysis suggested that IF deposition likely persisted at near constant rate from 3.8 to 1.8 Ga (Johnson and Molnar, 2019).…”
Section: Iron Formations Evidence Ferruginous Conditionsmentioning
confidence: 96%
“…"ferruginous") conditions in the deep ocean were spatially extensive and temporally pervasive, and continued through periods of Earth's history not typified by IF deposition (e.g. Canfield et al, 2008;Clarkson et al, 2016;Johnson and Molnar, 2019;Johnston et al, 2010;März et al, 2008;Planavsky et al, 2011;Poulton et al, 2015;Poulton and Canfield, 2011). However, the very low concentrations of iron in the current ocean point to fundamentally different redox conditions in the modern (oxic) as compared to past (anoxic) oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically precipitated sediments record the (bio)geochemistry of their aqueous environments (Derry and Jacobsen, 1990), and deeper marine strata from the Archean Eon (4.0-2.5 Ga) are dominated by iron formations (silica-rich chemical sediments with >15% iron) (Simonson and Hassler, 1996). The long-term, widespread deposition of iron formations suggests anoxic conditions and high iron concentrations in seawater, yet the accumulation of iron-rich sediments was likely triggered by a chemical change or (bio) geochemical process that induced mineral precipitation (Holland, 1984;Bekker et al, 2014;Johnson and Molnar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When examining the geologic record, the largest volumes of preserved IFs span the Late Archean to Paleoproterozoic, ending rather abruptly after 1.87 Ga (Gole and Klein, 1981; Trendall, 2002; age from Fralick et al., 2002). This record could reflect continuous IF deposition that is no longer evident due to preservation bias (Johnson & Molnar, 2019), or cessation of massive IF deposition after the GOE followed by brief IF resurgence ∼1.88 Ga (e.g., Bekker et al., 2014; Konhauser et al., 2017; Lyons et al., 2014).…”
Section: Introductionmentioning
confidence: 99%